Inovações curriculares: um estudo de caso do curso de Pós-Graduação Lato Sensu MBA gerenciamento de obras, tecnologia e qualidade da construção - Moraes, Leonardo Rodrigues de (2014)
This research was developed from a case study of the Post Sensu Lato that is offered by the Institute of Graduate Studies (IPOG). The objective of this research was to analyze the possible contributions of curriculum innovation for the postgraduate graduation courses in MBA Construction Management, Construction Technology and Quality, considering the current requirements for continuing qualification of engineers in Brazil, from the contributions of teachers and students of the same course. All research linked to this line of research Educator Training for Higher Education Curriculum Education PUC SP Program. The methodology was qualitative approach, working with the procedures of theoretical research, document analysis, questionnaires and interviews. The results show that the postgraduate graduation courses has a function to form to meet the demands of the market and therefore become Learning Areas. Other important issues that initially was thought to be the PBL curriculum paradigm that would bring to the course, its ability to innovate, but to conduct the search, especially fieldwork, hearing students and teachers, we believe it is just one of the PBL models can cause curricular innovations. We understand the birthing responses of students and teachers, there is a deep nexus of real possibilities for curricular innovations that can be perfectly applied in the course of MBA Construction Management, Construction Technology and Quality. Considering the central problem and the answers obtained, we concluded the research in affirming that it is perfectly possible to apply the course curriculum innovations in the study, either by PBL or another model. This application will bring, in our view, significant improvements in the curriculum and in their ability to innovate